On the Improvement of Default Forecast Through Textual Analysis - Cerchiello, Paola; Scaramozzino, Roberta (Frontiers in Artificial Intelligence, 2020)
Textual analysis is a widely used methodology in several research areas. In this paper we apply textual analysis to augment the conventional set of account defaults drivers with new text based variables. Through the employment of ad hoc dictionaries and distance measures we are able to classify each account transaction into qualitative macro-categories. The aim is to classify bank account users into different client profiles and verify whether they can act as effective predictors of default through supervised classification models.